Older Adults' Computer-Mediated Communication (CMC) Engagement Following COVID-19 and Its Impact on Access to Community, Information, and Resource Exchange: A Longitudinal, Qualitative Study. (20th October 2021) - Mikal, Jude P.; Wurtz, Rebecca; Grande, Stuart W.
Following COVID-19, the CDC asked individuals to social distance and state and local authorities nationwide began issuing curfews and recommendations to "shelter-in-place." Known to be more susceptible to the negative effects of COVID-19 and often coping with higher levels of social isolation, many worried that older adults' mental health would suffer. While computer-mediated communication (CMC) is on the rise among older adults, whether and how older adults leverage the social benefits of CMC remains underexplored. This study assesses older adults' CMC use after COVID and the impact of CMC engagement on access to connection, information, and resources. We follow 22 older adults over 6 weeks, using longitudinal qualitative surveys to study CMC use patterns and mental health outcomes. Results revealed that while older adults exhibited purpose-driven CMC engagement, limited integration into larger online communities restricted access to up-to-the-minute information, notably early in the pandemic. Longitudinal findings show progressively less engagement with online news and information, withdrawal from online social engagement, and a progressive relaxing of social distancing. This study sheds light on how best to reach older adults following disaster, and where older adults may be disadvantaged as social media becomes a modern "emergency broadcast system."